Pemulihan aktif lebih baik daripada pemulihan pasif untuk mengoptimalkan pemulihan tubuh pasca-latihan - Andriana, Laily Mita; Ratna Sundari, Luh Putu; Muliarta, I Made; Ashadi, Kunjung; Nurdianto, Arif Rahman (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
One of the efforts to prevent the overreaching condition is by doing a recovery phase after exercise. The quality and quantity of recovery influence the effectiveness of recovery. The effectiveness of recovery can be observed by heart rate and body temperature after recovery. This study aims to compare active recovery and passive recovery after moderate-intensity continuous training on heart rate and body temperature. The research method used is quasi-experimental and uses a two-group pre and post-test design. Based on the Pocock formula, the research subjects used were 40 women aged 24 years to 35 years. The data collected include heart rate and body temperature. The data analysis techniques used were normality test, treatment effect test (paired sample t-test), and difference test (independent samples t-test). The results showed that active recovery was better than passive recovery to optimizing post-exercise heart rate (p<0.05). Active recovery was better than passive recovery in optimizing body temperature (p<0.05). It was concluded that active recovery after moderate-intensity continuous training was better than passive recovery to optimize post-exercise recovery and prevent overreaching.